2018
DOI: 10.1007/s11033-018-4187-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of myostatin expression is associated with growth and muscle development in commercial broiler and DMC muscle

Abstract: Myostatin is a negative regulator of skeletal muscle growth. Muscle tissue is the largest tissue in the body and influences body growth. Commercial Avian broiler chickens are selected for high growth rate and muscularity. Daweishan mini chickens are a slow growing small-sized chicken breed. We investigated the relations between muscle (breast and leg) myostatin mRNA expression and body and muscle growth. Twenty chickens per breed were slaughtered at 0, 30, 60, 90, 120, and 150 days of age. Body and muscle weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…Recent researches reported in myostatin-null mice revealed that PI3K and apoptotic pathways were regarded as possible Myostatin targets and Myostatindeficiency in mice increases global gene expression at the Dlk1-Dio3 locus in the skeletal muscle (Chelh et al, 2009;Hitachi and Tsuchida, 2017;Lessard et al, 2018). Myostatin acts at key points during pre-and post-natal life of amniotes that ultimately determine the overall muscle mass of animals selected for high growth rate and muscularity (Aiello et al, 2018;Dou et al, 2018). Mutations in domestic animals have already demonstrated the impact of attenuating Myostatin activity on muscle development and a number of large animals, including cattle, sheep, goat, horse, pig, rabbit and chicken, display the double muscled phenotype or enlarged muscle mass due to mutations in the Myostatin gene (Aiello et al, 2018;Dou et al, 2018).…”
Section: Myostatinmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent researches reported in myostatin-null mice revealed that PI3K and apoptotic pathways were regarded as possible Myostatin targets and Myostatindeficiency in mice increases global gene expression at the Dlk1-Dio3 locus in the skeletal muscle (Chelh et al, 2009;Hitachi and Tsuchida, 2017;Lessard et al, 2018). Myostatin acts at key points during pre-and post-natal life of amniotes that ultimately determine the overall muscle mass of animals selected for high growth rate and muscularity (Aiello et al, 2018;Dou et al, 2018). Mutations in domestic animals have already demonstrated the impact of attenuating Myostatin activity on muscle development and a number of large animals, including cattle, sheep, goat, horse, pig, rabbit and chicken, display the double muscled phenotype or enlarged muscle mass due to mutations in the Myostatin gene (Aiello et al, 2018;Dou et al, 2018).…”
Section: Myostatinmentioning
confidence: 99%
“…Myostatin acts at key points during pre-and post-natal life of amniotes that ultimately determine the overall muscle mass of animals selected for high growth rate and muscularity (Aiello et al, 2018;Dou et al, 2018). Mutations in domestic animals have already demonstrated the impact of attenuating Myostatin activity on muscle development and a number of large animals, including cattle, sheep, goat, horse, pig, rabbit and chicken, display the double muscled phenotype or enlarged muscle mass due to mutations in the Myostatin gene (Aiello et al, 2018;Dou et al, 2018). The most recent research investigated the relations between muscle (breast and leg) myostatin mRNA expression and body and muscle growth among commercial broiler chickens (Dou et al, 2018).…”
Section: Myostatinmentioning
confidence: 99%
See 3 more Smart Citations